Application and effectiveness of Methylobacterium symbioticum as a biological inoculant in maize and strawberry crops - Torres Vera, Rocío; Bernabé García, Antonio José; Carmona Álvarez, Francisco José; Martínez Ruiz, Jesús; Fernández Martín, Félix (Folia microbiologica, 2024)
The effectiveness of Methylobacterium symbioticum in maize and strawberry plants was measured under different doses of nitrogen fertilisation. The biostimulant effect of the bacteria was observed in maize and strawberry plants treated with the biological inoculant under different doses of nitrogen fertiliser compared to untreated plants (control). It was found that bacteria allowed a 50 and 25% decrease in the amount of nitrogen applied in maize and strawberry crops, respectively, and the photosynthetic capacity increased compared with the control plant under all nutritional conditions. A decrease in nitrate reductase activity in inoculated maize plants indicated that the bacteria affects the metabolism of the plant. In addition, inoculated strawberry plants grown with a 25% reduction in nitrogen had a higher concentration of nitrogen in leaves than control plants under optimal nutritional conditions. Again, this indicates that Methylobacterium symbioticum provide an additional supply of nitrogen.
Keywords: Biostimulant; Methylobacterium; Biofertiliser; Nitrogen-fixing bacteria; Zea mays; Fragaria; Photosynthesis; Strawberry; jahodník; zemědělské plodiny; Nitrogen; Maize; dusík; fotosyntéza; Methylobacterium symbioticum; Crops, Agricultural; kukuřice setá